Karakteristik Sifat Mekanis Dan Fisik Tanah Lunak Di Kabupaten Rokan Hilir Berdasarkan Pengujian Dokenbo Dan Vane Shear - Abdullah Ihsan Alkubuwi; Muhamad Yusa; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Along with the times and the rapid growth of technology created by humans, many ideas and ideas from building experts have emerged to research further about the nature and characteristics of the soil according to their respective types. In accordance with the topic of this research, the type of soil that will be studied further is soft soil. This study aims to determine the statistical relationship between physical characteristics and mechanical characteristics based on the parameter values obtained from dokenbo dan vane shear. In this study, an experiment was conducted to find the characteristics of soft soil in Rokan Hilir Regency using dokenbo and vane shear tools directly in the field, it is hoped that dokenbo dan vane shear have a relationship that can be compared later. Furthermore, the physical properties of the soft soil will be tested in the laboratory in order to determine the property value of the soft soil itself. The test was carried out at 30 points spread over several locations in Rokan Hilir Regency. From this research, the shear strength (Su) of the dominant vane shear is 16-20 kPa, with an overall value range of 4-34 kPa. The dominant dokenbo penetration value range is 301-400 kN/m2, with an overall value range of 158-1430 kN/m2. The dominant dokenbo shear angle value range is 21 o-25 o, with an overall value range of 9-41 o. Based on the correlation results, the penetration value is directly proportional to the Su value, the correlation between penetration and shear angle has a very low relationship, the correlation between penetration and physical properties has a low relationship. Keywords: Soft soil, shear strength, Dokenbo